Boosting the sustainable development goals in a civil engineering bachelor degree program. Issue 8 (4th August 2021) - Gómez-Martín, M. Esther; Gimenez-Carbo, Ester; Andrés-Doménech, Ignacio; Pellicer, Eugenio
Abstract : Purpose: The purpose of this paper is to analyze the potential for implementing Sustainable Development Goals (SDGs) into the civil engineering bachelor degree in the School of Civil Engineering at Universitat Politècnica de València (Spain). Design/methodology/approach: All the 2019/2020 course syllabi were analyzed to diagnose at which extent each subject within the program curriculum contributes to achieving the different SDGs. Findings: The results show a promising starting point as 75% of the courses address or have potential to address targets covering the 2030 Agenda. This paper also presents actions launched by the School of Civil Engineering to boost the SDGs into the civil engineering curriculum. Originality/value: This paper presents a rigorous and systematic method that can be carried out in different bachelor degrees to find the subjects that have the potential to incorporate the SDGs into their program. This paper also presents actions launched by the Civil Engineering School to boost the SDGs into the civil engineering curriculum.